2008
DOI: 10.1371/journal.pbio.0060088
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of DNA Strand Exchange Mediated by Rhp51 Recombinase and Two Mediators

Abstract: In the fission yeast Schizosaccharomyces pombe, genetic evidence suggests that two mediators, Rad22 (the S. pombe Rad52 homolog) and the Swi5-Sfr1 complex, participate in a common pathway of Rhp51 (the S. pombe Rad51 homolog)–mediated homologous recombination (HR) and HR repair. Here, we have demonstrated an in vitro reconstitution of the central step of DNA strand exchange during HR. Our system consists entirely of homogeneously purified proteins, including Rhp51, the two mediators, and replication protein A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
97
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(104 citation statements)
references
References 48 publications
7
97
0
Order By: Relevance
“…Recent studies have revealed that the Swi5-Sfr1 complex stimulates both Rad51-mediated and Dmc1-mediated strandexchange reactions by activating the recombinases directly. Thus, Swi5-Sfr1 acts as an activator of the recombinases (Haruta et al, 2007;Kurokawa et al, 2008). Determining the crystal structures of Swi5 and Sfr1 is of importance because such molecular information will provide a better understanding of the function of Swi5 and Sfr1 in homologous recombination.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that the Swi5-Sfr1 complex stimulates both Rad51-mediated and Dmc1-mediated strandexchange reactions by activating the recombinases directly. Thus, Swi5-Sfr1 acts as an activator of the recombinases (Haruta et al, 2007;Kurokawa et al, 2008). Determining the crystal structures of Swi5 and Sfr1 is of importance because such molecular information will provide a better understanding of the function of Swi5 and Sfr1 in homologous recombination.…”
Section: Introductionmentioning
confidence: 99%
“…The Swi5-Sfr1 complex is an auxiliary protein for both Rad51 and Dmc1 (Akamatsu et al 2003(Akamatsu et al , 2007Ellermeier et al 2004). We demonstrated that Swi5-Sfr1 stimulates three-strand exchanges mediated in vitro by Rad51 and Dmc1 (Haruta et al 2006;Kurokawa et al 2008). We also discovered ) that both fission yeast and human Rad51 proteins can promote the formation and BM of HJs, with a four-strand exchange assay containing gDNA and its homologous ldsDNA (Supplemental Fig.…”
mentioning
confidence: 78%
“…1B). Swi5-Sfr1 complex and RPA were added to the reaction, both of which have been shown to stimulate the three-strand exchange reaction mediated by Rad51 or Dmc1 (Haruta et al 2006;Kurokawa et al 2008). In both 39-end and 59-end homology reactions,similar high amounts of JMs-especially fJMs corresponding to the s structure-were formed within 30 min after reaction initiation (Fig.…”
Section: Dmc1 Promotes a Dna Four-strand Exchange Reaction In A 59-tomentioning
confidence: 99%
See 1 more Smart Citation
“…These complexes are thought to stabilize and/or activate Rad51 filaments to promote the strand exchange reaction (Akamatsu et al 2003(Akamatsu et al , 2007Ellermeier et al 2004;Kurokawa et al 2008). Notably, the Swi5-Sfr1 complex exhibits very low mediator activity (i.e., this complex does not significantly help Rad51 to bind ssDNA that is already coated with RPA), but additional information on this complex, which is required for full levels of recombination (Akamatsu et al 2003;Ellermeier et al 2004), is lacking, although its sharply kinked structure has been determined by X-ray crystallography (Kuwabara et al 2012).…”
mentioning
confidence: 99%